Material and method selection for increasing the wear resistance of construction machines components - A. P. Scherbakov (Вестник СибАДИ)
Introduction. The article examines the problem of choosing a material and method for increasing the wear resistance of construction machines elements. The performance of construction machines is affected by the reliability of the parts used. The selection of materials for their manufacture allows to calculate the probability of how such elements will affect its ability to work and productivity.Materials and methods. In the process of determining the material and the method for increasing the wear resistance of construction machines, structural steels with various chemical compositions were selected: lowcarbon 08ps (as a model material), 10, 20.30, St3 and low-alloy steels 09G2S and 10HSND, as well as high-carbon steel 65G and boron steel 30MnB5. The methods as high temperature annealing, normalization, injection and high temperature release, thermocyclic processing, cold plastic deformation, thermocyclic processing of steels after cold plastic deformation were used.Results. During the experiment, it was found that both for low-carbon 08ps, 10, 20, 30, St3, and for low-alloy structural steels 09G2S and 10HSND, as well as for high-carbon steel 65G and for boron-containing steel 30MnB5, an increase in the number of TCT cycles (thermal cycling) leads to an increase in the strength properties of the metal. With an increase in the number of cycles over 3-6, the increase in strength properties slows down significantly. Conclusion. In contrast to heat treatment, TCO allows to identify the positive effect of alloying on strength and plastic properties to a greater extent. At the same time, significantly increasing the strength and plasticity, it is possible to obtain previously unattainable values of the work of destruction of alloy steels in the process of various types of loading. Accordingly, the preliminary preparation of steel for the production of individual elements of machines and mechanisms will increase their strength and wear resistance.